Innovative colorimetric approaches for sodium benzoate detection: methodological insights and quantification - Sreedevi Paramparambath (17346997) (2025)
Sodium Benzoate (SB) is a commonly used food additive to prevent food deterioration and spoilage, and it extends shelf life. However, maintaining SB levels within safe limits is crucial to avoid potential health risks. Beyond the food industry, SB is also widely employed in industrial applications, particularly as a corrosion inhibitor. The present study introduces a colorimetric sensor with three-dyes incorporated with a smartphone unit to provide relative RGB (red/blue/green) data. This developed sensor is highly selective and sensitive and the concentration of SB is quantified using the unique RGB values obtained from software on the phone. Chlorophenol red (CPR), Thymol blue (TB) and m-cresol purple solution (MCP) are the three dyes employed for the detection of SB in water at various experimental conditions. Utilizing the developed three-dye system, we obtained a LOD value of 1.85ppm, 2.71 ppm and 4.40ppm in CPR, TB and MCP dyes, respectively, in a 10–100 ppm detection range. In addition to standard testing, the practical applicability of the sensor was evaluated using real-world samples including soft drinks and industrial corrosion inhibitor solutions. The proposed sensor could be used for low-cost, rapid, and potable detection tool for SB levels in both food safety and environmental quality. Other Information Published in: Journal of Food Science and Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13197-025-06409-6